Pengembangan E-modul Sistem Koloid Berbasis Inkuiri Terbimbing Terintegrasi Al Quran untuk Kelas XI Madrasah Aliyah (MA) - Hafifah Azirah; Iryani Iryani (Universitas Negeri Padang, 2022)
The 2013 curriculum in chemistry learning demands that students to actively participate, skilled in the use of technology and communication so that the learning process is more interactive. This is also in accordance with the demands of the Fourth Industrial Revolution era. The application of 4IR in the field of education is the use of e-modules. This e-module is based on guided inquiry and is integrated with the verses of the Al Quran according to the claim of the West Sumatra Provincial Regulation No. 2 of 2019 and competence 1 in the 2013 curriculum. The goal of the research was to produce and reveal the validity of an E-Module based on Guided Inquiry and Integrated Quran on Colloidal System Topic for Madrasah Aliyah (MA). The type of research is educational design research that uses the Plomp model. This model has three stages, which are preliminary research, prototyping stage, and assessment. The research instrument used in the validity test is a questionnaire and to prove the validity value, the Aikens formula is used. The results of the study get the average value of e-module Aikens is 0,8643 which can be categorized as valid. With this e-module, it can support learning in the 2013 curriculum as well as a good learning resource, where students can learn independently and think critically.